Clinical Observation on Chiropractic Exercise Therapy for Infantile Cerebral Palsy - Jiarui LIU; Qiuyang XIANG; Li ZHOU; Lanli LI; Yihong CHEN; Ying ZHOU (康复学报)
Objective:To observe the clinical effect of chiropractic exercise therapy on infantile cerebral palsy.Methods:70 patients with infantile cerebral palsy were randomly assigned to the treatment group and control group with 35 patients in each group. The treatment group received chiropractic and exercise therapy, and the control group received pure exercise therapy once a day. The treatment course consisted of twenty days of chiropractic and exercise therapy, and complete treatment included two courses. GMFM-88 assessment scales were used to assess infantile gross motor function, and curative effect index of nimodipine was used to evaluate the clinical efficacy. Weight and food intake of infantum were collected before and after treatment, and the changes of their growth and development were analyzed.Results:After two courses of treatment, the GMFM-88 scale scores in the two groups were increased significantly (P<0.05), and weight and food intake scores in both groups were decreased significantly (P<0.05). There were significant differences in the GMFM-88 scale scores, weight and food intake scores between two groups after treatment (P<0.05). Curative effect of treatment group was superior to control group after treatment (P<0.05).Conclusion:Chiropractic exercise therapy can significantly improve motor development retardation of infantum with cerebral palsy, the curative effect of chiropractic exercise therapy is better than pure exercise therapy, and is worth for clinical spreading application.